Draft Annual Plan 1994-95, State Planning Commission, Tamil Nadu - Planning Commission (Planning Commission, 1993)
The annual plan for 1994-95 assumes significance as it will be the mid-year of the Eighth Plan arid the cumulative performance at the end of 1994-95 will largely determine the Success of the Eighth Plan. Tamil Nadu has made a good beginning in the first year (1992-93) of the Plan and it is a matter of satisfaction that the plan expenditure during 1992-93 was Rs. 1935 crores which represents art increase of Rs. 169 crores or 9.5 per cent over the approved plan outlay of Rs. 1,766 crores. The Agriculture Sector’s performance was remarkably good and the foodgrains production reached the level of 84.55 lakh tonnes. Electricity generation was maintained at a fairly high level of 16,958 MU and the State did hot impose, any power cut. Industrial production however received a set back but this was mainly due to macro economic factors operating at the national level such as recession and the credit squeeze over which the State has little control. The Annual Plan for 1993-94 envisages an outlay of Rs. 2,101 crores and the State is well poised for implementation of the Plan, in full measure. Available details on trends in the progress of implementation of schemes, and the plan expenditure during the first half of the year indicate that the performance of the State’s economy during the current year will continue to be satisfactory. The favourable monsoon and widespread rainfall in the State have brightened the prospects of a bumper crop. Tamil Nadu faced the fury of Nature for the second year in succession. Heavy rainfall and consequent flood, land slides arid cyclonic storms affected large parts of the State during September-December 1993, and caused extensive d.mage to life, property, standing crops and infrastructure such as roads, transmission lines, etc. Loss caused by the cyclonic storm is estimated at Rs. 666 crores. Massive relief, rehabilitation and restoration work has been initiated. The State Government has sought Central Assistance to meet the relief operations. It is against this background, Tamil Nadu has formulated the Annual Plan for 1994-95.
Draft Annual Plan 1994-95
Government of Tamil Nadu